DETERMINING THE PROFILE MODEL (PHYSICAL - SKILL) FOR PLAYERS IN HANDBALL SPECIALIZED CENTERS - Anwar Asaad Abdelghani; Prof Dr. Raed Mohammad Mshatat; Dr. Dhurgham Abdul Salam Neamah (Scholars Digest Publishing, 2024)
The aim of the research is to identify the level of performance (physical - skills) of the handball specialist centers, and to determine the model of the profile (physical - skills) of the players of the handball specialist centers. From here, the importance of the research emerged in drawing the profile network (profile) for the physical - skill performance of the players. Specialized handball centers, which can provide us with an evaluative model for the level of performance. The research problem is the lack of use of the lateral shape model in evaluating the level of performance (physical - skillful) of the players of the handball specialized centers The researchers used the descriptive survey method to achieve the research objectives. The research sample included players from specialized handball centers for the 2023/2024 sports season.
Keywords: Lateral shape model, physical performance, skills performance, Handball.